Cultivando saberes: diálogos sobre a produção de sementes de alface com estudantes de Agronomia do IFSULDEMINAS - Campus Inconfidentes - Franco, Fernanda Pereira (2018)
The motivation for this research arose from the experiences of IFSULDEMINAS - Campus Inconfidentes, together with the coexistence with family farmers and the assimilation of some of their needs, considering the agricultural production of the region and the technical assistance received by these farmers. The objective of this project was to create dialogic spaces for the construction of knowledge about the production of lettuce seeds with students from the Agronomic Engineering course of IFSULDEMINAS - Campus Inconfidentes. These spaces were built together with the students of the 7th period of the course, during two days of field, using an experimental research with six lettuce cultivars (Camila, Laurel, Luisa, Regina 71, Rubete and Verônica). The research was conducted in Inconfidentes. From this, a social study was carried out through the application of two problematizing questions, with the application of a questionnaire and a focus group. A leaflet on lettuce seed production was also made in a participatory manner. The evaluations of the social study were made using the frequency analysis methodology, while for the experimental research were performed variance analysis and tests of means for the characteristics of seed germination and vigor, mass of one thousand seeds (g) and mass of seed production (Kg.ha-1). The experimental design was completely randomized, with four replications and 10 plants per plot. It was possible to emphasize about the dialogical spaces that in relation to the importance of the dialogue, most of the students understand the dialogue as being of great importance. By participating in the activities proposed during this research, the students had access to different information about seed production, and from that point on, they could understand the production of lettuce seeds as a possibility to be studied and presented to the producer. Regarding the results of the experimental research, it is concluded that it is possible to produce the lettuce seed of the cultivars used in this experiment in the Inconfidentes region. It has been found that it is possible to produce an input, in this case the seed with quality and quantity for own use.